Clinical and Psychological Factors Associated with Addiction and Compensatory Use of Facebook Among Patients with Inflammatory Bowel Disease: A Cross-Sectional Study - Cury, Giovana Signorelli Astolfi [UNESP]; Takamune, Debora Mayumi [UNESP]; Herrerias, Giedre Soares Prates [UNESP]; Rivera-Sequeiros, Adriana; de Barros, Jaqueline Ribeiro [UNESP]; Baima, Julio Pinheiro [UNESP]; Saad-Hossne, Rogerio [UNESP]; Sassaki, Ligia Yukie [UNESP] (Taylor & Francis, 2022)
Background: Inflammatory bowel diseases are chronic conditions characterized by incapacitating symptoms, which can compromise patient’s quality of life and social interaction. As social media use is continuously increasing and Facebook is one of the most accessed social media worldwide, this study aimed to evaluate the use of Facebook and identify clinical and psychological factors associated with addiction and compensatory use among patients. Methods: This case-control study enrolled 100 outpatients and 100 healthy individuals, who were classified into the patient and control groups, respectively. Facebook use was evaluated using the questionnaire Psycho-Social Aspects of Facebook Use (PSAFU). The IBD Questionnaire and the 36-Item Short-Form Health Survey (SF-36) were used to measure Health-related quality of life. Anxiety and depression were evaluated using the Hospital Anxiety and Depression Scale; self-esteem, using the Rosenberg SelfEsteem scale. Results: The patient group included 54 patients with Crohn’s disease and 46 with ulcerative colitis. Facebook use was similar between the patient and control groups in all evaluated aspects (p=0.21). In the patient and the control groups, the compensatory use of Facebook was directly related to the symptoms of depression (patients: R = 0.22; p = 0.03; controls: R = 0.34; p = 0.0006) and inversely related to self-esteem scale (patients: R = −0.27; p = 0.006; controls: R = −0.37; p = 0.0001). Facebook addiction showed an inverse correlation with self-esteem (patients: R = −0.32; p = 0.001; controls: R = −0.24; p = 0.02) and quality of life (patients: IBDQ score, R = −0.30; p = 0.003; controls: SF-36 score, R = −0.29; p = 0.004). Conclusion: The use of Facebook was not different between study groups. Psychological aspects such as depression and low selfesteem were associated with the compensatory use of Facebook in both groups, which may be related to unsatisfactory personal aspects of social interaction.
Keywords: Addiction; Compensatory use; Facebook; Inflammatory bowel disease